Multifactorial criterion evaluation of lubrication efficiency and wear resistance of friction units operating under extreme operating conditions - O. Milanenko; A. Bobro (Проблеми трибології)
A new multifactor criterial approach to modifying lubricants by rheological properties and chemical composition is proposed in order to increase the lubricating ability of modified layers and wear resistance of friction units from the position of mixed lubrication conditions. Prevention of micro-EНD lubricating layer is achieved by a set of measures: implementation of stable micro-EHD lubrication by the criterion of lubrication mode; optimal viscosity class with an increase in the fraction of hydrodynamic pressure of modified layers relative to the contact pressure from micro-unevenness of rough surfaces by the pressure criterion; optimal type of lubricant by the rheological criterion; assessment of the appearance of a plastically deformed state by the criterion of plasticity; selection of the qualitative and quantitative chemical composition of active components in the lubricant to create durable modified layers with high structural adaptability and thermomechanical stability by the temperature criterion. A new concept for increasing lubricity and wear resistance for friction units operating in extreme operating conditions, using an appropriate criteria approach, takes into account: non-stationary friction conditions, the shape of local contact and friction kinematics, rheological properties of lubricating layers, contact temperature, and the composition of components in the lubricant